Prototype of LPG gas leakage detector using flame sensor and MQ-2 sensor - Harya Gusdevi; Ade Setya P; Puji Handini Zulaeha (Computer Science and Information Technologies, 2020)
The conversion of kerosene use in household to gas, in addition to the decision of the Republic of Indonesia minister in relation to the movement of kerosene to gas, gas also given an affordable price, how to use it more effectively. But the public is also expected to be careful about how to use it, because the gas is explosive and leaking causing unpleasant odor (gas leak) even a more dangerous side effect is the explosion of gas cylinders. To evercome these problems then need a tool that can detect gas leakage, in order to prevent gas leakage early. Therefore the authors designed a device that can detect gas leakage by using Sensor Mq-2 and will issue sound gas alarm warning leak by Modul ISD 1760, and will stop the gas flow from the tube to the stove using a Solenoid Valve. There is also a Flame Sensor’s hardware to detect a fire if there is a spark emerging and spraying water into spots that are likely to spark fire. All hardware will be in if using ATMega 328 microcontroller. Monitoring can use android smartphone, with the application that can send a warning to the mobile phone.